Preparation and application of MoSe2 quantum dot loaded titanium black nanotube array photo-anode
By using MoSe2 QD/TiO2 NTA photoanode material in the photoelectro-catalytic system, combined with interface regulation and domain-limiting catalytic strategies, the problems of low electron utilization and poor resistance gene reduction in the deep treatment of wastewater in traditional Chinese medicine are solved. , achieving efficient and low-energy consumption wastewater degradation and resistance gene removal effects.
Patent Information
- Application Number
- CN202411585985.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-08
- Publication Date
- 2025-02-18
- Estimated Expiration
- 2044-11-08
AI Technical Summary
When the existing photoelectric catalytic degradation system deeply treats pharmaceutical wastewater, the electron utilization rate is low, the energy consumption is high, and the ability to reduce resistance genes is poor, making it difficult to achieve deep removal of resistance genes in wastewater.
Using interface regulation and domain-limited catalytic synergistic strategies, the MoSe2 quantum dots are anchored to the surface of titanium oxide nanotubes by solvothermal method to form MoSe2 QD/TiO2 NTA photoanode material, regulate the heterojunction interface structure, and reduce the interface energy barrier. Improve carrier migration and transfer rates.
The photoelectrocatalytic performance is improved, and the efficient degradation of antibiotics and resistance genes in wastewater is achieved, and the mass transfer efficiency of electrode surface is improved, energy consumption is reduced, and catalytic stability is enhanced.
Smart Images

Figure CN119455986A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of environmental engineering technology, and relates to research on the preparation technology of molybdenum diselenide quantum dot-loaded titanium dioxide nanotube array electrode materials, and particularly to an innovation in a method of using the material as an anode to construct a photoelectric catalytic degradation system for degrading typical industrial wastewater. Background Art
[0002] The environmental pollution caused by pharmaceutical wastewater has attracted global attention. Eliminating the threat it poses to ecological security and human health is a current research hotspot and difficulty in the field of environmental engineering.
[0003] Photoelectrocatalytic technology is an efficient method for degrading organic pollutants. Its advantage lies in coupling photocatalysis and electrocatalysis through catalytic electrodes to achieve synergistic catalysis. The performance of photoelectrode catalytic materials plays a crucial role. Therefore, the research on the preparation of high catalytically active photoanodes and photoelectrocatalytic degradation mechanisms for antibiotics and resistance genes in wastewater is of great practical significance for achieving efficient degradation and detoxification of pharmaceutical wastewater. The articles “Efficient electrochemical oxidation of COVID-19 treatment drugs favipiravir by a novel flow-through Ti / TiO2-NTA / Ti4O7 anode”, “Cu2O on anodised TiO2 nanotube arrays:Aheterojunction photoanode for visible light assisted electrochemical degradation of pharmaceuticals in water” and “Effective degradation of aqueouscarbamazepine on a novel blue-colored TiO2 nanotube arrays membrane filteranode” respectively studied the use of electrode materials such as Ti / TiO2-NTA / Ti4O7, Cu2O modified TiO2 NTA, and defective TiO2 NTA for the degradation of favipiravir, ciprofloxacin, and carbamazepine. Although the above studies can improve the degradation ability of the photoanode for pharmaceutical wastewater, the electron utilization rate is low and the energy consumption is high during the deep treatment of pharmaceutical wastewater. At the same time, in the traditional photocatalytic degradation system ·OH has a poor ability to reduce resistance genes, making it difficult to achieve deep removal of resistance genes in wastewater. Therefore, it is necessary to develop an effective electrode material that can improve the mass transfer efficiency of the electrode surface and produce active species with selective degradation ability for resistance genes.
[0004] TiO2 nanotube array (TiO2 NTA) is an excellent photoelectrocatalytic material with a hollow and ordered spatial structure that meets the requirements of confined catalytic materials for the substrate. At the same time, a large number of oxygen vacancies on the surface can be used as anchoring points to enhance the stability of the loaded catalytic material. MoS2 is a typical transition metal disulfide with abundant sulfur active sites, catalytic stability and unique physicochemical properties (narrow band gap, presence of vacancies). However, the main electrocatalytic active sites of this type of material are the edges of MoS2, which are easily affected by surface adsorbed substances and inhibit the catalytic performance. Therefore, it is necessary to find alternative materials with similar physicochemical properties and better catalytic performance. MoSe2 is a semiconductor material with a two-dimensional layered structure. It is similar to molybdenum disulfide (MoS2) in structure and has the advantages of narrow band gap, excellent mechanical properties, anti-photocorrosion, moderate interlayer spacing and large specific surface area. In addition, since Se has metallic properties, it will enhance the conductivity of MoSe2 materials and effectively improve the carrier migration rate. If defect engineering and heterostructure construction strategies are combined and MoSe2 semiconductor is loaded into the nanotube cavity of TiO2 NTA photoanode, a confinement effect can be formed between the active site (MoSe2) and the defect site (TiO2 NTA oxygen vacancy), the heterojunction interface structure can be regulated, and a special energy band structure - Dirac cone - can be constructed. The synergistic charge transfer effect can increase the carrier migration conversion rate, reduce the interface energy barrier, and improve the photoelectrocatalytic performance.
[0005] Therefore, the present invention adopts the synergistic strategy of interface regulation and confined catalysis, uses the solvothermal method to anchor MoSe2 on the surface of sub-titanium oxide nanotubes, and regulates the heterojunction interface structure of the substrate and the substrate oxygen vacancy structure through the calcination method to form a sub-titanium oxide nanotube array (MoSe2QD / TiO2 NTA) photoanode material loaded with molybdenum diselenide quantum dots. The Fermi level of the system is regulated by the heterojunction interface structure, the interface energy barrier is reduced, the carrier transition and transfer rate are increased, and the photoelectrocatalytic performance of the material is improved. Based on MoSe2QD / TiO2 NTA, a photoelectrocatalytic degradation system is constructed, and the interface electric field and surface defect structure in the material structure are adjusted to promote the catalytic activity and catalytic stability of the photoanode, so as to achieve the goal of synergistically strengthening the mineralization and detoxification of the degradation system by using the confinement effect and the charge transfer effect. Summary of the invention
[0006] The present invention provides a method for preparing a molybdenum diselenide quantum dot-loaded titanium oxide nanotube array electrode, and is applied to a photoelectrocatalytic degradation system to degrade antibiotics and resistance genes in wastewater. MoSe2 QD / TiO2 NTA photoelectrocatalytic materials are prepared by anchoring MoSe2 using defect sites (oxygen vacancies) on the surface of a TiO2 NTA substrate. The heterojunction interface structure of the material is regulated by the preparation conditions to optimize the interface electric field. The Fermi level of the system is adjusted by the synergistic effect between the active site (MoSe2 QD) and the defect site (TiO2 NTA), the interface energy barrier is reduced, and the electron transition and transfer rate are increased. At the same time, TiO2 NTA produces a confinement effect on the MoSe2 QD loaded on its surface, which can effectively increase the d-band center of Ti and reduce · The Gibbs free energy of OH desorption is beneficial to the generation and desorption of active oxidative species in the system.
[0007] The technical solution of the present invention:
[0008] A method for preparing a MoSe2 quantum dot-loaded titanium dioxide nanotube array photoanode, the steps are as follows:
[0009] Step 1: Refer to "Unraveling the reinforced photoelectrocatalytic activity and stability via unique configuration of P 3+ -O v -Ti 3+ in TiO 2-x In the article "nanotube array", titanium dioxide nanotube array electrodes (TiO2NTA) were prepared in situ on the surface of a flat titanium electrode plate by electro-etching method.
[0010] Step 2: Using TiO2 NTA as the substrate, selecting Se with reducing ability and sodium molybdate as the reaction precursors with a molar ratio of 3:1 to 2:1, using 1-ethyl-3-methylimidazolium acetate ionic liquid as the reaction solvent, controlling the concentration of sodium molybdate to 0.01-0.1 mol / L, using the solvothermal method, the reaction temperature is 140-200°C, the reaction time is 8-24h, and after the solvothermal reaction is completed, the electrode material is taken out for annealing (air atmosphere, 400°C reaction for 2h), and finally referring to “Unraveling thereinforced photoelectrocatalytic activity and stability via unique configuration of P 3+ -O v -Ti 3+ in TiO 2-xThe electrode was electrochemically reduced by the "nanotube array" method to obtain MoSe2 quantum dots loaded titanium dioxide nanotube array photoanode (MoSe2 QD / TiO2 NTA) photoelectrocatalytic material.
[0011] The invention discloses an application of a MoSe2 quantum dot-loaded titanium oxide nanotube array photoanode in the treatment of pharmaceutical wastewater. The obtained MoSe2 QD / TiO2 NTA electrode is used as a photoanode, a titanium mesh is used as a cathode, and the electrode spacing is 1-2 cm to construct an electrochemical reaction system. The distance between the light source and the photoanode is 5-12 cm, and the wavelength range of the light source is 420-780 nm visible light. The system is operated in a constant current mode with a current density of 1-10 mA / cm 2 . Using a DC power supply, the simulated wastewater containing 100μg / L-50mg / L concentrations of ciprofloxacin hydrochloride, sulfamethoxazole, 5-fluorouracil, and 2,4,6-trichlorophenol and the actual pharmaceutical wastewater containing the above pollutants (COD range 300-1000mg / L) were used as the target water bodies. The reaction time was 30min, and the removal rate of the target pollutants in the effluent was maintained at more than 98%. At the same time, for the actual pharmaceutical wastewater, the COD removal rate was 60-94%.
[0012] Beneficial effects of the present invention: The present invention adopts a synergistic strategy of interface regulation and confined catalysis, utilizes oxygen vacancies (defective structures) on the surface of the TiO2NTA substrate to capture MoSe2 quantum dots (MoSe2 QD), regulates the interface structure between MoSe2 QD and the substrate through solvent thermal regulation, enhances the interaction between the active sites and the substrate, and forms a stable MoSe2 QD-loaded TiO2 NTA (MoSe2 QD / TiO2 NTA) photoanode material. The Fermi level of the system is regulated by the heterojunction interface structure, the interface energy barrier is reduced, and the photogenerated carrier transition is improved, thereby achieving the purpose of improving the catalytic activity of the material. In step 2, the excess elemental Se is at the defect site (Ti 3+ ) to generate MoSe2 and participate in regulating the electric field at the heterojunction interface, optimizing Ti 3+ The charge distribution at the site can reduce its tendency to transform to a high-valence state during the catalytic process and improve the catalytic stability of the system. During the catalytic reaction, the confinement effect of TiO2 NTA on MoSe2 QD and the charge transfer effect mediated by the interfacial electric field can synergistically regulate the migration and transformation path of electrons in the system, reduce the reaction energy barrier of active species, and effectively increase the amount of active species produced in the system. Based on MoSe2 QD / TiO2 NTA, a photoelectrocatalytic degradation system is constructed, and the confinement effect and charge transfer effect are used to synergistically enhance the photoelectrocatalytic degradation and mineralization performance, thereby achieving deep removal of difficult-to-degrade organic matter in wastewater. BRIEF DESCRIPTION OF THE DRAWINGS
[0013] Figure 1TEM and corresponding EDS scans of MoSe2 QD / TiO2 NTA-003-12, where (a) is the TEM image of MoSe2 QD / TiO2 NTA-003-12, (b) is the Ti element scan in MoSe2 QD / TiO2 NTA-003-12, (c) is the O element scan in MoSe2QD / TiO2 NTA-003-12, (d) is the Mo element scan in MoSe2 QD / TiO2 NTA-003-12, and (e) is the Se element scan in MoSe2 QD / TiO2 NTA-003-12.
[0014] Figure 2 Comparison diagram of oxygen vacancies in MoSe2 QD / TiO2 NTA-003-12 and TiO2 NTAESR.
[0015] Figure 3 These are the XPS graphs of MoSe2 QD / TiO2 NTA-003-12 and TiO2 NTA, where (a) is the XPS total spectrum of MoSe2 QD / TiO2NTA-003-12 and TiO2 NTA, and (b) is the Ti2p spectrum of MoSe2 QD / TiO2 NTA-003-12 and TiO2 NTA. DETAILED DESCRIPTION
[0016] The specific implementation of the present invention is described in detail below in combination with the technical scheme and the accompanying drawings.
[0017] Example 1
[0018] MoSe2 QD / TiO2 NTA electrode material preparation:
[0019] Reference "Unraveling the reinforced photoelectrocatalytic activity andstability via unique configuration of P 3+ -O v -Ti 3+ in TiO 2-xThe method for preparing the electro-etching solution in the article "nanotube array" is as follows: ethylene glycol, ammonium fluoride and water are mixed in a mass ratio of 90:5:5, and magnetically stirred until the ammonium fluoride is dissolved to form an electro-etching solution. A titanium flat plate electrode is used as the anode and placed in an electro-etching reactor. A lead oxide electrode is used as the cathode and is placed on both sides of the titanium flat plate electrode, with an electrode spacing of 5 cm. The constant voltage is 35V and the operation is performed for 3 hours. The reaction temperature is controlled by a constant temperature water bath, and the reaction temperature control range is 20-25°C. After the reaction is completed, the etched titanium flat plate electrode is taken out, placed in deionized water, and ultrasonicated for 10 minutes, and then placed in an oven at 60°C to obtain a sub-titanium oxide nanotube array electrode (TiO2 NTA).
[0020] TiO2 NTA was used as the substrate, Se with reducing ability and sodium molybdate were selected as the reaction precursors with a molar ratio of (3:1), 1-ethyl-3-methylimidazolium acetate ionic liquid was used as the reaction solvent, the concentration of sodium molybdate was 0.03 mol / L, the solvothermal method was adopted, the reaction temperature was 160℃, the reaction time was 12h, and after the solvothermal reaction, the electrode material was taken out for annealing (air atmosphere, 400℃ reaction for 2h), and finally referred to “Unraveling the reinforced photoelectrocatalytic activity and stability via unique configuration of P 3+ -O v -Ti 3+ in TiO 2-x The electrode was electrochemically reduced by the "nanotube array" method. The specific method was as follows: the annealed electrode was used as the cathode, the lead oxide electrode was used as the anode, and a 10% wt ammonium sulfate aqueous solution was used as the electrolyte. The constant current was 3 mA / cm 2 , electrochemical reduction for 2 minutes to obtain MoSe2 QD / TiO2 NTA-003-12 photoelectrocatalytic material.
[0021] The above method was used to change the concentration of sodium molybdate in the solvent thermal reaction to 0.02, 0.05 and 0.1 mol / L to prepare a series of MoSe2 QD / TiO2 NTA electrode materials (named MoSe2 QD / TiO2 NTA-002-12, MoSe2QD / TiO2 NTA-005-12 and MoSe2 QD / TiO2 NTA-010-12).
[0022] In addition, a series of MoSe2QD / TiO2NTA electrode materials (named MoSe2QD / TiO2NTA-003-8, MoSe2QD / TiO2NTA-003-16 and MoSe2QD / TiO2NTA-003-24) were prepared by changing the solvent thermal time to 8, 16 and 24 h using the above method.
[0023] Comparative Example 1
[0024] The same preparation method as in Example 1 was used, but the solvent of the solvothermal reaction was changed, and the 1-ethyl-3-methylimidazolium acetate ionic liquid was replaced with deionized water to prepare MoSe2 QD / TiO2 NTA-003-12-H2O.
[0025] Comparative Example 2
[0026] The same preparation method as in Example 1 was used to replace the MoSe2 material with MoS2. The preparation method was as follows: 0.175 g of thiourea and 0.145 g of Na2MoO4·2H2O were dispersed in 100 ml of deionized water and stirred for 30 min. 0.117 g of citric acid was added to the above solution. The magnetic stirring was continued for 10 min to form a uniform mixture. TiO2 NTA was immersed in the above solution and placed in a reactor. The reaction was carried out at 200°C for 12 h. After the solvothermal reaction was completed, the electrode material was taken out for annealing (air atmosphere, 400°C for 2 h). The annealed electrode was used as the cathode, lead oxide as the anode, and a 10% wt ammonium sulfate aqueous solution was used as the electrolyte. The constant current was 3 mA / cm 2 , electrochemical reduction for 2 minutes to obtain MoS2 QD / TiO2 NTA photoelectrocatalytic material.
[0027] Example 2
[0028] Electrochemical performance test:
[0029] The MoSe2 QD / TiO2 NTA series electrode materials were used as working electrodes, platinum sheets of the same size were used as counter electrodes, and calomel electrodes were used as reference electrodes to construct a three-electrode system. The electrolyte was 0.02 mol / L Na2SO4 aqueous solution. The electrochemical workstation was used to test the electrochemical impedance spectroscopy (EIS) and open circuit voltage (OCP) of the MoSe2 QD / TiO2 NTA series electrode materials.
[0030] The EIS spectra of this series of electrode materials show that as the concentration of sodium molybdate increases, the conductivity of the material first increases and then decreases, and the conductivity of MoSe2 QD / TiO2 NTA-003-12 is the best. This shows that the MoSe2 loading can effectively control the efficiency of electron migration on the electrode surface. In addition, in the OCP test, it was found that the potential difference generated by the MoSe2QD / TiO2 NTA-003-12 electrode after irradiation with visible light is the largest, indicating that the appropriate interface structure relationship between MoSe2 and TiO2 NTA can effectively improve the system's ability to migrate photogenerated carriers.
[0031] Example 3
[0032] Typical simulated pharmaceutical wastewater degradation test by photoelectrocatalytic system:
[0033] MoSe2 QD / TiO2 NTA-002-12, MoSe2 QD / TiO2 NTA-003-12, MoSe2 QD / TiO2 NTA-005-12 and MoSe2 QD / TiO2 NTA-010-12 were used as photoanodes, titanium mesh was used as cathode, and the electrode spacing was 1 cm. The photoelectrocatalytic system was constructed. The light source was 10 cm away from the photoanode. The wavelength range of the light source was 420-780 nm visible light. The system was operated in a constant current mode with current densities of 1, 3, 5 and 10 mA / cm, respectively. 2 . Using simulated wastewater containing 20 mg / L 2,4,6-trichlorophenol as the target water body, repeated degradation tests were carried out. The single reaction time was 30 minutes, and the reaction effluent was taken once every 10 minutes. The reaction effluent was filtered with a 0.22μm water membrane and 2 mL was taken and put into a liquid phase vial. After unified collection, it was used to test the degradation performance. The same degradation test was repeated 10 times. After the reaction was completed, 10 mL of the reaction effluent was taken and filtered with a 0.22μm water membrane as the TOC test sample.
[0034] The concentration of 2,4,6-trichlorophenol was measured by ultra-high performance liquid chromatography. The test results showed that as the current density increased, the system's ability to remove target pollutants also increased. When the current density exceeded 5 mA / cm 2 When the reaction time is 30 minutes, the removal rate of target pollutants in the effluent water exceeds 99%. MoSe2 QD / TiO2NTA-003-12 photoanode is 3mA / cm 2 Under the same conditions, the removal rate of the target pollutant in the effluent water was 99% after 30 minutes of reaction. The change pattern of the TOC removal rate of the MoSe2 QD / TiO2 NTA-003-12 photoanode was the same as that of the target pollutant. The current density was 1, 3, 5, and 10 mA / cm 2The TOC removal rates were 36%, 55%, 61%, and 88% when the current density of MoSe2 QD / TiO2 NTA was increased. The results of 10 repeated tests showed that there was no significant attenuation in the removal rates of the target pollutants and TOC. The test results showed that the greater the current density of MoSe2 QD / TiO2 NTA, the higher the removal rates of the target pollutants and TOC.
[0035] Example 4
[0036] Degradation tests on different types of simulated pharmaceutical wastewater:
[0037] MoSe2 QD / TiO2 NTA-003-8, MoSe2 QD / TiO2 NTA-003-12, MoSe2 QD / TiO2 NTA-003-16 and MoSe2 QD / TiO2 NTA-003-24 were used as photoanodes, titanium mesh was used as cathode, and the electrode spacing was 1 cm. The photoelectrocatalytic system was constructed. The light source was 10 cm away from the photoanode. The wavelength range of the light source was 420-780 nm visible light. The system was operated in a constant current mode with a current density of 10 mA / cm 2 . The degradation test was carried out with simulated wastewater containing 20 mg / L concentration of ciprofloxacin hydrochloride, sulfamethoxazole and 5-fluorouracil as the target water body. The reaction time was 30 minutes, and the reaction water was taken once every 10 minutes. The reaction water was filtered with a 0.22μm water membrane and 2 mL was taken and put into a liquid phase vial. After being collected, it was used to test the degradation performance. After the reaction was completed, another 20 mL of the reaction water was taken and filtered with a 0.22μm water membrane as a TOC test sample.
[0038] The concentration of target pollutants was determined by ultra-high performance liquid chromatography. The test results showed that the removal rates of MoSe2 QD / TiO2 NTA-003-8, MoSe2 QD / TiO2 NTA-003-12, MoSe2 QD / TiO2 NTA-003-16 and MoSe2 QD / TiO2 NTA-003-24 photoanodes for ciprofloxacin hydrochloride, sulfamethoxazole and 5-fluorouracil were all above 99%. Among them, the removal rates of TOC by MoSe2 QD / TiO2 NTA-003-12 photoanode were 92%, 83% and 76%, respectively. This shows that this type of electrode material has high degradation and mineralization performance for typical drug pollutants in pharmaceutical wastewater in the photoelectrocatalytic degradation system.
[0039] Example 5
[0040] Actual pharmaceutical wastewater degradation test:
[0041] MoSe2 QD / TiO2 NTA-003 was used as the photoanode and titanium mesh as the cathode. The electrode spacing was 1 cm. The photoelectrocatalytic system was constructed. The light source was 10 cm away from the photoanode. The wavelength range of the light source was 420-780 nm visible light. The system was operated in a constant current mode with a current density of 10 mA / cm 2 The degradation test was carried out with the effluent of the biological unit of actual pharmaceutical wastewater (COD of 300, 500, and 1000 mg / L, respectively). The reaction time was 2 hours, and the reaction effluent was taken once every 10 minutes. The taken reaction effluent was directly put into a 10 mL centrifuge tube and collected uniformly for testing COD removal performance. In addition, the content of antibiotic resistance genes in the wastewater before and after the reaction was investigated.
[0042] The national standard method was used to test the effluent COD. The test results showed that the removal rates of the MoSe2 QD / TiO2 NTA-003 electrode for the actual pharmaceutical wastewater COD were 83%, 79% and 81%, respectively. This shows that the photoanode has a high removal performance for typical drugs in actual pharmaceutical wastewater. The test results of the antibiotic resistance gene content in the wastewater before and after the reaction showed that the photoanode had a removal rate of 99% for the antibiotic resistance gene in the wastewater, which can effectively reduce the potential harm to the ecological environment caused by the discharge of wastewater into natural water bodies.
[0043] The MoSe2 QD / TiO2 NTA-003-12-H2O prepared in Comparative Example 1 and the MoS2QD / TiO2 NTA photoanode materials prepared in Comparative Example 2 were used in Examples 2-5, respectively. The comparison results are as follows:
[0044] The electrochemical performance test results show that MoSe2 QD / TiO2 NTA-003-12-H2O and MoS2QD / TiO2 NTA have no obvious response to visible light, that is, there is no obvious potential difference in the electrode OCP test results before and after visible light irradiation. At the same time, the EIS test shows that the conductivity of MoSe2 QD / TiO2 NTA is better than that of MoSe2 QD / TiO2 NTA-003-12-H2O and MoS2 QD / TiO2 NTA comparative materials.
[0045] The degradation test results of typical simulated pharmaceutical wastewater degradation by photoelectrocatalytic system showed that under the same operating conditions, MoSe2 QD / TiO2 NTA-003-12-H2O and MoS2 QD / TiO2 NTA could degrade 20 mg / L 2,4,6-trichlorophenol simulated wastewater at 5 mA / cm 2 The current density and the removal rate of target pollutants in the effluent were only 59% and 44% after 30 minutes of reaction.
[0046] The degradation test results of different types of simulated pharmaceutical wastewater showed that under the same operating conditions, the removal rates of MoSe2QD / TiO2NTA-003-12-H2O and MoS2 QD / TiO2 NTA for 20 mg / L concentration of ciprofloxacin hydrochloride, sulfamethoxazole and 5-fluorouracil simulated wastewater were 76% and 54%, 49% and 32%, and 39% and 34%, respectively.
[0047] The test results of actual pharmaceutical wastewater degradation showed that under the same operating conditions, the COD removal rates of MoSe2 QD / TiO2NTA-003-12-H2O and MoS2 QD / TiO2 NTA for the effluent of actual pharmaceutical wastewater biological unit (COD were 300, 500, and 1000 mg / L, respectively) were 27% and 18%, 22% and 13%, and 14% and 8%, respectively.
[0048] The above comparative test results can illustrate that the solvothermal reaction can effectively regulate the interface structure between MoSe2 QD and the substrate, enhance the interaction between the active sites and the substrate, and form a stable MoSe2 QD / TiO2NTA photoanode material. MoSe2 has a similar structure to molybdenum disulfide (MoS2), and has the advantages of a narrow band gap, excellent mechanical properties, resistance to photocorrosion, moderate interlayer spacing and large specific surface area. Since Se has metallic properties, it will enhance the conductivity of MoSe2 materials and effectively improve the carrier migration rate. Therefore, the loading of MoSe2 QD can effectively improve the spectral response range, conductivity and carrier migration ability of the substrate.
Claims
1. A method for preparing a MoSe2 quantum dot-loaded titanium dioxide nanotube array photoanode, characterized in that: Here are the steps: Step 1: Using an electro-etching method, preparing an electro-etching solution, and in-situ preparing a titanium oxide nanotube array electrode TiO2 NTA on the surface of a flat titanium electrode plate; Step 2: Using TiO2 NTA as a substrate, selecting Se with reducing ability and sodium molybdate as reaction precursors, the molar ratio of the two is 3:1-2:1, using 1-ethyl-3-methylimidazolium acetate ionic liquid as a reaction solvent, controlling the concentration of sodium molybdate to be 0.01-0.1 mol / L, using a solvothermal method, a reaction temperature of 140-200°C, a reaction time of 8-24h, after the solvothermal reaction is completed, taking out the electrode material for annealing, and performing electrochemical reduction treatment on the electrode to obtain MoSe2 quantum dot-loaded sub-titanium oxide nanotube array photoanode MoSe2 QD / TiO2 NTA.
2. The preparation method according to claim 1, characterized in that: The annealing conditions are: air atmosphere, 400°C for 2h.
3. The preparation method according to claim 1, characterized in that: The electro-etching solution is prepared as follows: ethylene glycol, ammonium fluoride, and water are mixed in a mass ratio of 90:5:5, and magnetic stirring is performed until the ammonium fluoride is dissolved to form an electro-etching solution.
4. The preparation method according to claim 1, characterized in that: The electrochemical reduction treatment process is as follows: the annealed electrode is used as the cathode, the lead oxide electrode is used as the anode, and a 10% wt ammonium sulfate aqueous solution is used as the electrolyte at a constant current of 3 mA / cm 2 , electrochemical reduction for 2 min.
5. Application of a MoSe2 quantum dot-loaded titanium dioxide nanotube array photoanode in the treatment of medical wastewater, characterized in that: The MoSe2 QD / TiO2 NTA electrode was used as the photoanode and the titanium mesh as the cathode. The electrode spacing was 1-2 cm to construct an electrochemical reaction system. The light source was 5-12 cm away from the photoanode. The system was operated in a constant current mode with a current density of 1-10 mA / cm 2 , treat pharmaceutical wastewater.
6. The use according to claim 5, characterized in that: The light source is visible light with a wavelength range of 420-780nm.
7. The use according to claim 5, characterized in that: Use DC power supply.
8. The use according to claim 5, characterized in that: Pharmaceutical wastewater is wastewater containing ciprofloxacin hydrochloride, sulfamethoxazole, 5-fluorouracil, and 2,4,6-trichlorophenol.
9. The use according to claim 5, characterized in that: The concentration of pharmaceutical wastewater is 100μg / L-50mg / L.
Citation Information
Patent Citations
MoSe2 nanosheet composite fireworks-shaped TiO2 nanorod array and preparation method thereof
CN105833886A
MoS2 / TiO2NTs heterojunction photo-electro-catalyst substituting noble metal Pt sheet for hydrogen evolution and preparation method of MoS2 / TiO2NTs heterojunction photo-electro-catalyst
CN106582721A
Method for synthesizing polyhedral hollow MoS2 (molybdenum disulfide) particle by ion liquid-assisted hydrothermal type
CN106809880A
Preparation method of TiO2 nanotube and MoSe2 nanosheet composite material
CN109989088A
Electrochemical preparation method of nano-composite molybdenum diselenide modified titanium dioxide nanotube array
CN110327945A